2022
DOI: 10.1155/2022/7671169
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Study on Ultrasonographic Diagnosis and Postoperative Comprehensive Nursing of Rectal Cancer in Preoperative Staging

Abstract: The aim of this study is to evaluate the value of ultrasonography in preoperative T staging of rectal cancer and to study the effect of psychological nursing and colostomy nursing in patients with rectal cancer after colostomy. In this study, a retrospective comparative analysis was conducted on 41 patients with colostomy after rectal cancer surgery who had been treated in a hospital from June 2020 to June 2021 and 41 patients who only had general nursing. By analysis, 42 cases were detected by TRUS. Ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%